TRANSFORMASI LITERASI PEMUDA DESA MELALUI PELATIHAN KONTEN DIGITAL BERBASIS WEBSITE: STUDI KASUS DI SAMURA, KARO - Tarigan, Karisma Erikson; Simarmata, Petrus (Indonesian Collaboration Journal of Community Services (ICJCS), 2025)
This community service initiative seeks to improve digital literacy among young individuals by providing training in website content creation in Samura Village, Kabanjahe Subdistrict, Karo Regency.  Preliminary findings indicated that local teenagers exhibited a constrained capacity for critically evaluating digital information and ethically generating contextual material.  A participatory workshop was organised to tackle this issue, incorporating interactive lectures, group discussions, practical writing exercises, and digital distribution through blog platforms.  The engagement included 20 participants aged 18 to 23 and utilised the Seven Pillars of Information Literacy as the educational framework.  The evaluation results demonstrate a considerable enhancement in participants' comprehension of digital material, their capacity to generate informative local content, and their enthusiasm for establishing a sustainable literacy community.  The program documentation validated participants' enthusiasm and the initiative's pertinence to the village community's requirements.  Consequently, the program demonstrated efficacy in cultivating critical thinking abilities and digital literacy at the grassroots level